HSV-2 Infection Enhances Zika Virus Infection of Primary Genital Epithelial Cells Independently of the Known Zika Virus Receptor AXL - Gornalusse, Germán G.; Zhang, Mengying; Wang, Ruofan; Rwigamba, Emery; Kirby, Anna C.; Fialkow, Michael; Nance, Elizabeth; Hladik, Florian; Vojtech, Lucia (Frontiers in Microbiology, 2022)
Zika virus (ZIKV) is transmitted to people by bite of an infected mosquito and by sexual contact. ZIKV infects primary genital epithelial cells, the same cells targeted by herpes simplex virus 2 (HSV-2). HSV-2 seroprevalence is high in areas where ZIKV is endemic, but it is unknown whether HSV-2 increases the risk for ZIKV infection. Here, we found that pre-infecting female genital tract epithelial cells with HSV-2 leads to enhanced binding of ZIKV virions. This effect did not require active replication by HSV-2, implying that the effect results from the immune response to HSV-2 exposure or to viral genes expressed early in the HSV-2 lifecycle. Treating cells with toll-like receptor-3 ligand poly-I:C also lead to enhanced binding by ZIKV, which was inhibited by the JAK-STAT pathway inhibitor ruxolitinib. Blocking or knocking down the well-studied ZIKV receptor AXL did not prevent binding of ZIKV to epithelial cells, nor prevent enhanced binding in the presence of HSV-2 infection. Blocking the α5 integrin receptor did not prevent ZIKV binding to cells either. Overall, our results indicate that ZIKV binding to genital epithelial cells is not mediated entirely by a canonical receptor, but likely occurs through redundant pathways that may involve lectin receptors and glycosaminoglycans. Our studies may pave the way to new interventions that interrupt the synergism between herpes and Zika viruses.